Sequential one-pot synthesis of N-sulfonyl spiroaziridine oxindoles from spiroepoxy oxindoles. Issue 25 (8th June 2021) - Biswas, Anurag; Saleh, SK Abu; Hazra, Atanu; Debnath, Subhas Chandra; Hajra, Saumen
Abstract : A sequential one-pot direct strategy for N -sulfonyl spiroaziridine oxindoles has been developed from spiroepoxy oxindoles with excellent yields by regioselective amination of spiroepoxide and a subsequent ring enclosure reaction of amino alcohol. Abstract : The N -sulfonyl spiroaziridine oxindole is a recently developed versatile precursor in the synthesis of a wide range of 3, 3-disubstituted spirooxindoles. It is usually prepared in three steps from isatin and needs costly and hardly available sulfinimides and hazardous peracid. A sequential and one-pot direct strategy for the synthesis of terminal N -sulfonyl spiroaziridine oxindoles has been developed under ambient conditions with excellent yields (up to 95%) from easily accessible spiroepoxy oxindoles by regioselective amination with aqueous ammonia and a subsequent ring enclosure reaction of the resulting 1, 2-amino alcohol using easily available sulfonyl chloride and a base. Other salient features of the protocol include inexpensive substrate requirement and the ease of isolation of the desired product by performing single column chromatographic purification after two consecutive steps.